2015
DOI: 10.1039/c5mb00129c
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy modeling reveals a dynamic self-sustaining network of the GLI transcription factors controlling important metabolic regulators in adult mouse hepatocytes

Abstract: The GLI transcription factors, GLI1, GLI2, and GLI3, transduce Hedgehog and non-hedgehog signals and are involved in regulating development and tumorgenesis. Surprisingly, they were recently found to modulate important functions of mature liver. However, less is known about their mutual interactions and possible target genes in mature hepatocytes. To get a deeper insight into these interactions cultured mouse hepatocytes were transfected with siRNAs against each GLI factor. RNA was extracted at different times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…) . This data confirmed in human tumors the role of sonic hedgehog pathway in zonation previously observed in mouse models . On the other hand, β‐catenin exon 3 mutated HCA harbored a perivenous program because Wnt/ β‐catenin was a key signaling pathway known to be involved in liver zonation and in the maintenance of a perivenous network of genes .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…) . This data confirmed in human tumors the role of sonic hedgehog pathway in zonation previously observed in mouse models . On the other hand, β‐catenin exon 3 mutated HCA harbored a perivenous program because Wnt/ β‐catenin was a key signaling pathway known to be involved in liver zonation and in the maintenance of a perivenous network of genes .…”
Section: Discussionsupporting
confidence: 84%
“…(18) This data confirmed in human tumors the role of sonic hedgehog pathway in zonation previously observed in mouse models. (30)(31)(32)(33) On the other hand, b-catenin exon 3 mutated HCA harbored a perivenous program because Wnt/ b-catenin was a key signaling pathway known to be involved in liver zonation and in the maintenance of a perivenous network of genes. (21,22) Moreover, as ASL and ASS1 belong to the arginine synthesis pathway, these results suggested that arginine metabolism and urea cycle were mainly activated in periportal area and potentially controlled by sonic hedgehog pathway whereas glutamine synthesis were activated in perivenous area mainly by Wnt/b-catenin pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding liver metabolism, we recently showed that the regulation of the IGF-axis (insulin-like growth factor) in mature hepatocytes is controlled by Hh signaling ( Matz-Soja et al, 2014 ). Moreover, we were also able to show that the TFs GLI1, GLI2 and GLI3 form a unique self-stabilizing network in hepatocytes and regulate several metabolic genes, including lipid associated factors ( Schmidt-Heck et al, 2015 ). Therefore, in this study, we have focused on the alterations in lipid metabolism as a consequence of hepatic Hh signaling modulations in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 83%
“…To address this aim, a mouse model with a conditional hepatocyte-specific deletion of Smo in adult mice was established, in order to avoid interference with developmental effects of Hh signaling. For the in vitro investigations, we used RNA interference (RNAi) technology to knock down several genes of the Hh pathway in cultured hepatocytes ( Böttger et al, 2015 ; Schmidt-Heck et al, 2015 ). The results of our investigations clearly show that the Hh pathway is a strong regulator of lipid metabolism in the adult liver.…”
Section: Introductionmentioning
confidence: 99%
“…Further support is provided by the stimulatory effect of Ptch1 knockdown on Clock and Nr1d2 expression because the recently discovered dynamic selfsustaining network of GLI transcription factors led to the prior upregulation of Gli1 and Gli3. 14,35 Moreover, the FANTOM4 database 36 revealed specific binding sites for GLI factors within the respective clock genes, as illustrated in a transcriptomic output graph for the 3 Gli factors (Fig. 7A).…”
Section: A B C D E Gli3mentioning
confidence: 94%